Inter-Rater Reliability to the Assessment of Ramus Relationship of Mandibular Impacted Third Molar Among Denitsts: An Orthopantomographic Study - Iqra Ayub, Maryam Rehman, Maria Nawaz, Maria Jabbar, Hira Butt, Fahmina Jamil, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the inter-rater reliability to the assessment of ramus relationship of mandibular impacted third molar among denitsts. Methodology: A cross sectional comparative study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore after obtaining ethical clearance from ethical committee of Sharif Medical Research Centre (SMRC) in which dentists from three different specialties namely; Oral Pathology, Endodontics and Prosthodontics were included as raters. The study was conducted from December 2020 to February 2021. A total of 21 Orthopantomograms were assigned to each rater for assessing the ramus relationship of impacted third molar. The classification for angle of impaction used was Winter`s classification. The raters were provided with the OPGs and a proforma for recording their observations. Results: The level of agreement regarding the ramus relationship of impacted third molars observed on the Orthopantomograms between rater 1 and rater 2 was fair (κ=0.366 ,p=0.022). The agreement was also fair between rater 1 and rater 3 (κ=0.300, p=0.094). Conclusion: There was a fair agreement in assessment of ramus relation of the impacted mandibular molars of rater 1 with rater 2 and 3 where majority of the class 2 and class 3 relations were rated similarly by both the raters as Keywords: Inter-rater reliability, Cohen Kappa, Impacted third molar, Orthopantomogram, Ramus relationship